POTENSI USAHA PENGOLAHAN MINYAK ATSIRI DAUN CENGKEH DI KECAMATAN SIPORA SELATAN KABUPATEN KEPULAUAN MENTAWAI - Pramono Sasongko; Washington Washington; KGS Ahmadi (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
Clove (Syzigium aromaticum) is a spice plant which commonly used as raw material in cigarette, food and beverage, pharmaceutical, perfume and insecticide industries. All parts of the clove plant contain of essential oils. However, in Sipora District, Mentawai Islands, who have the majority of clove plantation businesses was use the flower part only. Fallen clove leaves with a potential of 15.9 tons/week only become plantation waste. Therefore, this study was conducted to determined the business potential of essential oils and economic value addition of clove leaves by using a purposive sampling survey method on clove farmers/entrepreneurs in the Sipora district. The results showed that 87.91% of cloves in the South Sipora Sub-district agreed to develop a waste distillation process. Meanwhile, 12.09% were not agree. The essential oil from clove leaves produced has physical characteristics of yellow-brown color, an average refractive index of 1.531, and an average yield of 2.13%. Prediction of the economic value of the estimated business income received is Rp. 921,600,000.00/year, R/C ratio of 1.79, NPV with a value of Rp. 778,730,880.00 BEP of 266 kg product and BEP of price of Rp. 42,525,092.45. IRR MARR 10% by 12% and Payback Period for 2 years 8 months. Moreover, the utilization of clove leaves as essential oil raw material in Sipora District, Mentawai Islands Regency provided some benefit